Nanoparticles promote in vivo breast cancer cell intravasation and extravasation by inducing endothelial leakiness - Peng, Fei; Setyawati, Magdiel Inggrid; Tee, Jie Kai; Ding, Xianguang; Wang, Jinping; Nga, Min En; Ho, Han Kiat; Leong, David Tai (Nature nanotechnology, 2019)
While most cancer nanomedicine is designed to eliminate cancer, the nanomaterial per se can lead to the formation of micrometre-sized gaps in the blood vessel endothelial walls. Nanomaterials-induced endothelial leakiness (NanoEL) might favour intravasation of surviving cancer cells into the surrounding vasculature and subsequently extravasation, accelerating metastasis. Here, we show that nanoparticles induce endothelial leakiness through disruption of the VE-cadherin-VE-cadherin homophilic interactions at the adherens junction. We show that intravenously injected titanium dioxide, silica and gold nanoparticles significantly accelerate both intravasation and extravasation of breast cancer cells in animal models, increasing the extent of existing metastasis and promoting the appearance of new metastatic sites. Our results add to the understanding of the behaviour of nanoparticles in complex biological systems. The potential for NanoEL needs to be taken into consideration when designing future nanomedicines, especially nanomedicine to treat cancer.